Pengaruh Pengetahuan Perpajakan Persepsi Dan Motivasi Terhadap Berkarir Di Bidang Perpajakan Dengan Self Efficacy Sebagai Variabel Moderasi Pada Mahasiswa Jurusan Akuntansi Perpajakan Fakultas Ekonomi Dan Bisnis Universitas Putra Indonesia “YPTK” - Putri Vinta Wulandari; Berta Agus Petra; Dodi Suryadi (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study aims to analyze the effect of tax knowledge, perception, and motivation on career interest in taxation with self-efficacy as a moderating variable among accounting students specializing in taxation at the Faculty of Economics and Business, Universitas Putra Indonesia “YPTK”. This research used a quantitative approach with a survey method. The population consisted of 52 undergraduate accounting students from the 2022 cohort who chose taxation as their concentration. The sampling technique used convenience sampling with a total sample of 52 respondents. Data analysis was conducted using descriptive statistics and multiple linear regression with classical assumption tests and hypothesis testing using SPSS 26 software. The results indicate that tax knowledge, perception, and motivation do not significantly influence career interest in taxation. Furthermore, self-efficacy does not moderate the relationship between tax knowledge and career interest in taxation. These findings suggest that internal factors among students have not fully encouraged interest in pursuing careers in taxation, highlighting the need for improved career exposure and practical learning experiences in taxation education.